2013
DOI: 10.1098/rsif.2013.0413
|View full text |Cite
|
Sign up to set email alerts
|

Design of composite scaffolds and three-dimensional shape analysis for tissue-engineered ear

Abstract: Engineered cartilage is a promising option for auricular reconstruction. We have previously demonstrated that a titanium wire framework within a composite collagen ear-shaped scaffold helped to maintain the gross dimensions of the engineered ear after implantation, resisting the deformation forces encountered during neocartilage maturation and wound healing. The ear geometry was redesigned to achieve a more accurate aesthetic result when implanted subcutaneously in a nude rat model. A non-invasive method was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 23 publications
0
45
0
2
Order By: Relevance
“…For example, the reconstruction of the ear has become a well-known challenge in tissue engineering. Early studies have employed scaffolds in the shape of an ear that are produced from animal or human derived cartilage [53,58,59,61,63,64]. However, after implantation and eventual scaffold degradation, the ear is often found to collapse or deform [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the reconstruction of the ear has become a well-known challenge in tissue engineering. Early studies have employed scaffolds in the shape of an ear that are produced from animal or human derived cartilage [53,58,59,61,63,64]. However, after implantation and eventual scaffold degradation, the ear is often found to collapse or deform [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, resorbable biomaterials suffer from the fact that regenerated tissues often collapse and become deformed due to the loss of structure [58][59][60][61][62]. For example, for several decades, research on ear reconstruction from engineered cartilage has shown that biomaterial implants eventually collapse and become deformed as the implanted scaffolds break down and resorb [63]. However, recent successful approaches have relied on the use of resorbable collagen scaffolds embedded with permanent titanium wire supports [53,64,65].…”
Section: Introductionmentioning
confidence: 99%
“…125 Similarly, Cervantes et al prepared an auricular mold through stereo-parallel printing and embedded a titanium wire frame and collagen solution in the mold to construct tissue-engineered composite ear scaffolds. 124 Collectively, these studies show that 3D printing technology has greatly facilitated the development and advancement of tissue-engineered ear scaffolds.…”
Section: D Printing Of Auriclesmentioning
confidence: 96%
“…123 Some research teams have used 3D printing technology to prepare complex auricular molds and then used impression molding to create tissue-engineered auricular constructs. 97,124,125 Liu et al 97 prepared an ear-shaped resin mold with CAD and 3D printing technologies and pressed PLA-coated PGA into the mold to construct an ear-shaped scaffold. The authors showed that the PLA coating increased the mechanical properties of the PGA structure and demonstrated the feasibility of using CAD and 3D printing technologies to construct an ear-shaped scaffold through impression molding.…”
Section: D Printing Of Auriclesmentioning
confidence: 99%
“…Recent advances in the understanding of nanobiomaterials and nanotechnology have released a promising perspective for intelligent biomaterials and devices such as the bone [2,65], the valve [66], the vessel [67], and the artificial ear [68]. 3DP as a newly emerging technology is a kind of an effective tool to obtain such tissues or devices.…”
Section: Performance Of 3dp For Nanobiomaterialsmentioning
confidence: 99%